Modified LUO High Gain DC-DC Converter With Minimal Capacitor Stress for Electric Vehicle Application - J. Divya Navamani; A. Geetha; Dhafer Almakhles; A. Lavanya; Jagabar Sathik Mohamed Ali (IEEE Access, 2021)
The vigorous growth of electric vehicles in the field of automobile paves the way for the development of dc-dc converter. A novel high gain super Luo dc-dc converter is proposed in this article. A modification is suggested in the topology when the converters are cascaded for high gain. This suggested modification can be applied to any topology for reliable capacitor. The presented converter adds boosting (voltage multiplier) cell before the load to expand the voltage conversion ratio. This converter renders remarkable features like extended voltage gain, low voltage stress on power switches, minimal capacitor stress and less component count. The operating principle and steady-state analysis of the proposed topology is presented. The main feature of the proposed topology is reduced capacitor stress which is evaluated by reliability study with military handbook MIL-HDBK-217F. The significance of minimal capacitor stress with the failure of the capacitor is elaborated. Simulation on the derived topology is carried out with Matlab/Simulink and it validates the theoretical results. Furthermore, the proposed topology is extended with dual output which makes the restructured converter suitable for Electric vehicle application and the simulation of the dual output topology is performed and studied. The experimental results obtained from the 50 W prototype validate the complete steady-state analysis performed on the proposed topology.